The Pulmonary Metastasectomy in Colorectal Cancer cohort study: Analysis of case selection, risk factors and survival in a prospective observational study of 512 patients. (5th May 2021) - Treasure, Tom; Farewell, Vernon; Macbeth, Fergus; Batchelor, Tim; Milošević, Mišel; King, Juliet; Zheng, Yan; Leonard, Pauline; Williams, Norman R.; Brew‐Graves, Chris; Fallowfield, Lesley; ,
Abstract: Aim: We wanted to examine survival in patients with resected colorectal cancer (CRC) whose lung metastases are or are not resected. Methods: Teams participating in the study of Pulmonary Metastasectomy in Colorectal Cancer (PulMiCC) identified potential candidates for lung metastasectomy and invited their consent to join Stage 1. Baseline data related to CRC and fitness for surgery were collected. Eligible patients were invited to consent for randomization in the PulMiCC randomized controlled trial (Stage 2). Sites were provided with case report forms for non‐randomized patients to record adverse events and death at any time. They were all reviewed at 1 year. Baseline and survival data were analysed for the full cohort. Results: Twenty‐five clinical sites recruited 512 patients from October 2010 to January 2017. Data collection closed in October 2020. Before analysis, 28 patients with non‐CRC lung lesions were excluded and three had withdrawn consent leaving 481. The date of death was known for 292 patients, 136 were alive in 2020 and 53 at earlier time points. Baseline factors and 5‐year survival were analysed in three strata: 128 non‐randomized patients did not have metastasectomy; 263 had elective metastasectomy; 90 were from the randomized trial. The proportions of solitary metastases for electively operated and non‐operated patients were 69% and 35%. Their respective 5‐year survivals were 47% and 22%. Conclusion: Survival without metastasectomy was greater than widely presumed. Difference in survival appeared to be largely related to selection. No inference can be drawn about the effect of metastasectomy on survival in this observational study.